RERATA VOLUME TROMBOSIT DI DIABETES MELITUS (Mean Platelet Volume in Diabetes Mellitus) - Maria Enrica; Nina Tristina; Anna Tjandrawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Diabetes Mellitus (DM) is a state of chronically hyperglycemia, which is caused by impaired insulin secretion and function. Thealteration in coagulation system in DM patients served as the basic etiology of macro and micro vascular complication. Platelets are oneof the factors that have a role in the coagulation system and undergo pathological changes in DM patients. Mean Platelet Volume (MPV)is an indicator of platelet function and activation. Larger platelets have more dense and more reactive pro coagulant granules. The aimof this study was to know whether there were differences in MPV between DM patients compared to medical check-up participants atthe Dr. Hasan Sadikin Hospital, Bandung.. The research used analytical descriptive, retrospective data. The inclusion criteria of thisresearch was DM patients and medical check up participants whose serum fasting glucose and two (2) hours post prandial serum glucosewere within the normal range. The data were taken from medical records of DM patients and medical check up participants. The datawere further analyzed with SPSS ver. 15 program using unpaired T-test. In this study, no significant difference between DM patientsand medical check up participants (p>0.05) was found. It can be concluded that Mean Platelet Volume if used as single, can not predictvascular complication in DM patients.